Our Bodies Belong to God : Organ Transplants, Islam, and the Struggle for Human Dignity in Egypt - Hamdy, Sherine, 1975- (University of California Press, 2012)
Why has Egypt, a pioneer of organ transplantation, been reluctant to pass a national organ transplant law for more than three decades? This book analyzes the national debate over organ transplantation in Egypt as it has unfolded during a time of major social and political transformation--including mounting dissent against a brutal regime, the privatization of health care, advances in science, the growing gap between rich and poor, and the Islamic revival. Sherine Hamdy recasts bioethics as a necessarily political project as she traces the moral positions of patients in need of new tissues and o.